Obstetric and perinatal outcomes in pregnancies conceived with donor versus partner sperm: a systematic review and meta-analysis - Liu, Junjie; Dai, Yanpeng; Song, Zuozhe; Sun, Xintao; Lv, Dongdong; Zhao, Dehua (Frontiers in Endocrinology, 2025)
BackgroundMale-related factors contribute to 30-40% of infertility cases, with donor sperm serving as a critical solution for severe male infertility or paternally inherited genetic disorders. While cryopreservation ensures virological safety, concerns persist regarding sperm DNA damage, oxidative stress, and epigenetic impacts on embryogenesis. Previous studies have shown inconsistent evidence regarding obstetric and perinatal outcomes using donor versus partner sperm. This meta-analysis aimed to compare these outcomes to guide evidence-based clinical decisions.MethodsTo identify studies published up to December 2024, we systematically search Embase, PubMed, Scopus, Wanfang, Web of Science, and China National Knowledge Infrastructure (CNKI). Studies investigating obstetric and perinatal outcomes using donor versus partner sperm were included regardless of the conception method. Adjusted estimates were prioritized, but crude estimates were utilized when necessary. Given the clinical and methodological heterogeneity, random-effects models were utilized to pool relative risks (RRs) and their 95% confidence intervals (CIs).ResultsThis analysis included 64 studies. Donor sperm was linked to better clinical pregnancy rates (RR 1.27, 95% CI 1.08–1.48) and decreased incidences of biochemical pregnancy (RR 0.85, 95% CI 0.81–0.88), miscarriage (RR 0.91, 95% CI 0.84–1.00), very preterm birth (RR 0.88, 95% CI 0.80–0.96), and very low birth weight (RR 0.89, 95% CI 0.81–0.98) compared with partner sperm. However, donor sperm conceptions exhibited increased risks of preeclampsia (RR 1.35, 95% CI 1.06–1.74) as well as pregnancy-induced hypertension (RR 1.19, 95% CI 1.05–1.36). For other outcomes, including gestational diabetes mellitus, ectopic pregnancy, placental abruption, placenta previa, large and small for gestational age, preterm birth, high and low birth weight, perinatal death, stillbirth, neonatal death, and congenital anomalies, no significant disparities were observed.ConclusionsDonor sperm offers improved pregnancy outcomes for severe male infertility or paternally inherited genetic disorders but is linked to elevated risks of preeclampsia and pregnancy-induced hypertension. Additional studies are required to explore potential mechanisms and design specific interventions.